0322 Cancer incidence in firefighters in sweden – preliminary findings from an updated cohort study. (21st August 2017) - Kullberg, Cecilia; Andersson, Tomas; Gustavsson, Per; Selander, Jenny; Tornling, Göran; Gustavsson, Annika; Bigert, Carolina
Abstract : Objectives: Firefighters are potentially exposed to carcinogens during work, such as benzene, benso(a)pyrene, arsenic, asbestos and silica dust. There are previous studies indicating an increased cancer risk among firefighters. The aim was to study risk of cancer in Swedish firefighters. Methods: We updated a previous cohort study of firefighters in Stockholm, comprising 1 080 men who worked at least 1 year as a firefighter during 1931–1983. They were followed regarding cancer incidence (in the National Cancer Register) from 1958–2012, adding 26 years of follow-up compared to the previous study. We also updated the information of employment duration, by annual records at the fire stations. We calculated standardised incidence ratios (SIR) with the male population in Stockholm as reference. Results: The overall cancer incidence was low (SIR=0.81, 95% CI=0.71–0.91), but there was a trend of increasing cancer incidence with increasing employment duration (p=0.03). There was an increased incidence of stomach cancer (SIR=1.89, 95% CI=1.25–2.75). The risk was significantly low for prostate cancer (SIR=0.68, 95% CI=0.52–0.87) and for malignant melanoma of the skin (SIR=0.30, 95% CI=0.06–0.88). Conclusions: We found no increased cancer incidence overall in Swedish firefighters, although the increasing incidence with increasing work duration indicates a possible carcinogenic effect of exposures at work. The cause of the increased incidence of stomach cancer is uncertain but could possibly be due to exposure to asbestos or silica dust, although this is quite speculative.